(untitled) (Zaporizhzhia Historical Review, 2021)
The article investigates new approaches in comprehending historical experience and the lessons of revolutionary period of 1917-1920th in Ukraine. The author comes to a conclusion that by now many of the past events, phenomena and tendencies have acquired more precise estimation than several years ago.